The Implementation of One Village One Product (OVOP) Program in Sambas Regency - Rusdiono, Rusdiono; Sudagung, Adityo Darmawan (Policy & Governance Review, 2024)
This paper examines the local government's implementation of village development policy at the borderlands, aiming to address the research gap by explaining the implementation of public policy through a case study of the One Village One Product (OVOP) program in Sambas Regency, Indonesia, which shares a border with Sarawak, Malaysia. We provide academic contributions to the field of public policy at the intersection of village development and border studies by explaining the local experience of implementing public policy. Additionally, the study provides practical recommendations for stakeholders in both public and private sectors to enhance OVOP programs following the best practices learned from other countries. The study, conducted from August to October 2023, employed qualitative research methods through observation and 15 interviews with government officials, the regency and village levels, and the local figures. Relevant documents were also collected and analyzed. The study found that two models of policy implementation applied in the research setting. In most villages, the OVOP program implemented the dominant top-down models due to the independent work of regency government officials and inadequate collaboration. The bureaucracy only provides short-term assistance and empowerment while hindering the aspirations of the private and community sectors to participate. At the same time, a hybrid model is exercised in one village where local stakeholders, the village government, and private and community sectors collaborate based on their sense of belonging toward "home" with less intervention from the regency government. The study recommends enhancing regular on-site or online communication and active collaboration between all stakeholders in the regency and the village level to improve OVOP program implementation in Sambas Regency.